2012
DOI: 10.5755/j01.ms.18.1.1342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Changes of the Structure of Foundry Bentonites on Their Binding Properties

Abstract: In this paper, the effects of the examination of the structure of calcium bentonites, activated by sodium carbonate, applied in the foundry industry as a binding agent for moulding sands, subjected to the effects of high temperature, were presented. The examination was conducted with the use of the infrared spectroscopy (FTIR) and X-ray analysis (XRD). In addition, the montmorillonite contents in the bentonite sample was determined with the use of the modern,
Cu(II)-TET complex method and the technologi…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The lost of structural water of bentonite occurred above 500°C. Similar results were also obtained by Zymankowska-Kumon et al (2012). They found that the structure of the smectite completely collapsed due to the lost of structural water at temperature of 700°C.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The lost of structural water of bentonite occurred above 500°C. Similar results were also obtained by Zymankowska-Kumon et al (2012). They found that the structure of the smectite completely collapsed due to the lost of structural water at temperature of 700°C.…”
Section: Introductionsupporting
confidence: 83%
“…The basal spacing (d 001 ) of bentonite and heat treated forms as the function of temperature (Table 4) indicates that the temperature slightly alters the basal spacing of the bentonite, however, if the temperature further increases to 600°C, the bentonite structure disappears. As mentioned in the previous section, the temperature has a significant effect on the structural water of the bentonite, the evaporation of structural water will alter the basal spacing of bentonite (Sarikaya et al, 2000;Zymankowska-Kumon et al, 2012). Completely lost of the structural water will destroy the MMt characteristic.…”
Section: Resultsmentioning
confidence: 89%
“…In pure bentonite, peak of kaoline exists in this region, which disappeared after the thermal treatment and substituted with an amorphous band, which indicates the transformation of kaoline to amorphous metakaolinite. Heating the bentonite clay causes its dehydration, which completes at 650 • C and further increase in the temperature leads to its dehydroxylation [25]. The transformation of kaoline to metakaolinite is associated with dehydration of clay and it increases the clay reactivity for easily alumina extraction by acids or alkalis [22,26].…”
Section: Resultsmentioning
confidence: 99%
“…Although the general heat-induced effects on the montmorillonite structure have been examined intensively, the effects of heat on moisture transport and, therefore, on the binding properties of bentonite-bonded moulding sands were subject to only very few studies (Holtzer et al, 2011;Bobrowski & Grabowska, 2012;Zymankowska-Kumon et al, 2012). Likewise, effects of cyclic reuse on the properties of moulding sand are far from being known satisfactorily.…”
Section: Introductionmentioning
confidence: 99%